HADITS-HADITS ASMAAUN AL-NABI MUHAMMAD SAW (Suatu Analisis Berdasarkan Kritik Matan dan Sanad) - Moh Abd Azis (Jurnal Ushuluddin Adab dan Dakwah, 2019)
This paper, entitled "Hadiths about Asmaun al-Prophet Muhammad SAW, (an analysis based on the criticism of the eyes), discusses the subject matter, namely how the quality of the traditions about Asmaun al-Prophet Muhammad Saw. In the research of hadith, the writer uses the maudhu'i method. In general, this research aims to collect the rules of internal criticism of hadith (naqd dakhiily / naqd batiiny) with the subject of hadiths. Applied criticism is expressed starting from the aspect of standardization (ratio) of hadithic information, testing the validity of texts and testing the multiplicity of doctrinal substances for the purposes of formulating shari'iyyah evidence. The author takes one path from the history of Imam At-Tirmidhi to be examined and finally it can be concluded that there are no things that can damage the credibility of sanad and hadith observations. So it can be stated that the hadith is of authentic quality. That means that its accuracy and status can be justified.